Associations of Ambulatory Blood Pressure With Urinary Caffeine and Caffeine Metabolite Excretions. Issue 3 (March 2015) - Guessous, Idris; Pruijm, Menno; Ponte, Belén; Ackermann, Daniel; Ehret, Georg; Ansermot, Nicolas; Vuistiner, Philippe; Staessen, Jan; Gu, Yumei; Paccaud, Fred; Mohaupt, Markus; Vogt, Bruno; et al.
<x xml:space="preserve">Abstract</x> Intake of caffeinated beverages might be associated with reduced cardiovascular mortality possibly via the lowering of blood pressure. We estimated the association of ambulatory blood pressure with urinary caffeine and caffeine metabolites in a population-based sample. Families were randomly selected from the general population of Swiss cities. Ambulatory blood pressure monitoring was conducted using validated devices. Urinary caffeine, paraxanthine, theophylline, and theobromine excretions were measured in 24 hours urine using ultrahigh performance liquid chromatography tandem mass spectrometry. We used mixed models to explore the associations of urinary excretions with blood pressure although adjusting for major confounders. The 836 participants (48.9% men) included in this analysis had mean age of 47.8 and mean 24-hour systolic and diastolic blood pressure of 120.1 and 78.0 mm Hg. For each doubling of caffeine excretion, 24-hour and night-time systolic blood pressure decreased by 0.642 and 1.107 mm Hg (both P values <0.040). Similar inverse associations were observed for paraxanthine and theophylline. Adjusted night-time systolic blood pressure in the first (lowest), second, third, and fourth (highest) quartile of paraxanthine urinary excretions were 110.3, 107.3, 107.3, and 105.1 mm Hg, respectively (P trend <0.05). No associations of urinary excretions with diastolic blood pressure were generally found, and theobromine excretion was not associated with blood pressure. Anti-hypertensive therapy, diabetes mellitus, and alcohol consumption modify the association of caffeine urinary excretion with systolic blood pressure. Ambulatory systolic blood pressure was inversely associated with urinary excretions of caffeine and other caffeine metabolites. Our results are compatible with a potential protective effect of caffeine on blood pressure.